APLIKASI TEORI CONDITIONING-REINFORCEMENT-SCAFFOLDING BERBANTUAN BAHAN AJAR MASTERY LEARNING PADA MATA KULIAH TEORI GRUP UNTUK MENINGKATKAN KEMAMPUAN PEMBUKTIAN MATEMATIS MAHASISWA - Mokhammad Ridwan Yudhanegara; Budi Hari Priyanto; Karunia Eka Lestari (Department of Mathematics Education, Universitas Kuningan, 2017)
AbstractGroup Theory course is contained the definitions, proof of theorem, and lemma so that in order to understand it, the students must have a good mathematical proofing ability. Furthermore, this article examines the comparative improvement of students' mathematical proofing abilities in the course of Group Theory. Comparisons were performed on three groups chosen purposively by subject matching techniques. The result of the research shows that at 95% level of confidence there is a difference in the improvement of students' mathematical proofing ability between those who get learning through the application of CRS theory with mastery learning materials, with students who get learning through CRS theory application and students who get learning through the application of constructivism theory.Keyword: Mathematical Proofing Ability, Conditioning, Reinforcement, Scaffolding, Mastery Learning